Mobile advertising: A systematic literature review and future research agenda. (6th July 2021) - Jebarajakirthy, Charles; Maseeh, Haroon Iqbal; Morshed, Zakir; Shankar, Amit; Arli, Denni; Pentecost, Robin
Abstract: The purpose of this research is to review the extant literature on mobile advertising systematically and to carry out a comprehensive analysis of research in this emerging field. Accordingly, this paper synthesises the literature on mobile advertising in terms of theories, contexts, characteristics and methodology to analyse the development of mobile advertising research over time. The literature review shows that mobile advertising research has transitioned from text message‐based SMS advertisements into internet‐based smartphone advertising. Furthermore, based on the synthesis, we have developed a conceptual framework that shows the antecedents, mediators and consequences of mobile advertising. Additionally, we have identified some overlooked areas and proposed some insightful research directions to advance this field of research. This review contributes to the mobile marketing literature, specifically to the mobile advertising literature.